1998
DOI: 10.1017/s0022112098002419
|View full text |Cite
|
Sign up to set email alerts
|

Mean-flow scaling of turbulent pipe flow

Abstract: Measurements of the mean velocity profile and pressure drop were performed in a fully developed, smooth pipe flow for Reynolds numbers from 31×103 to 35×106. Analysis of the mean velocity profiles indicates two overlap regions: a power law for 60<y+<500 or y+<0.15R+, the outer limit depending on whether the Kármán number R+ is greater or less than 9×103; and a log law for 600<y+<0.07R+. The log law is only evident if the Reynolds number is greater than approximately 400×103 (R+&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

48
562
3
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 670 publications
(619 citation statements)
references
References 0 publications
48
562
3
6
Order By: Relevance
“…This makes an impression that at present the reached accuracy of the available data on near-wall turbulent profiles is simply insufficient for the obtaining of a convincing unique conclusion about the real form of the mean-velocity profile in the intermediate layer of not-too-small and not-too-large values of z. However it seems also that great (and continued to grow) scatter of experimental values for the coefficients A, B and B (1) and for the limits of the logarithmic layer (cf., e.g., the strongly differing results of [84] and [85] which both asserted that their data are precise), contradicts to the idea of an universal overlap layer with logarithmic velocity profile having always the same constant coefficients. Barenblatt et al [89] remarked in this respect that found in [85] too low value K = 0.38 of von Kärmän constant contradicts the logarithmic-law universality.…”
Section: Xt) = A(t)f[x/l(t)]mentioning
confidence: 83%
See 4 more Smart Citations
“…This makes an impression that at present the reached accuracy of the available data on near-wall turbulent profiles is simply insufficient for the obtaining of a convincing unique conclusion about the real form of the mean-velocity profile in the intermediate layer of not-too-small and not-too-large values of z. However it seems also that great (and continued to grow) scatter of experimental values for the coefficients A, B and B (1) and for the limits of the logarithmic layer (cf., e.g., the strongly differing results of [84] and [85] which both asserted that their data are precise), contradicts to the idea of an universal overlap layer with logarithmic velocity profile having always the same constant coefficients. Barenblatt et al [89] remarked in this respect that found in [85] too low value K = 0.38 of von Kärmän constant contradicts the logarithmic-law universality.…”
Section: Xt) = A(t)f[x/l(t)]mentioning
confidence: 83%
“…Experimental studies of nearwall turbulent flows continue to be popular and recently several such investigations claiming to be quite accurate were carried out but this did not clarify the situation. Here we will only mention often cited recent papers by Zagarola and Smits [84] and Österlund et al [85] which both stated that their data confirm the validity of the logarithmic law (1) and both gave rise to a controversy.…”
Section: Xt) = A(t)f[x/l(t)]mentioning
confidence: 94%
See 3 more Smart Citations